2022
DOI: 10.48550/arxiv.2201.04184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of spin-orbit interaction and electron correlations in strontium titanate

Abstract: We show that the bottom of the conduction band in SrTiO3 is formed by the Kramers doublet of states with finite angular momentum involving a spin-orbit-coupled superposition of all three t2g orbitals of Ti. Analysis of electron correlations based on the Hubbard model shows that superconductivity may be mediated by the orbital entanglement of electrons due to the Mott-Hund's coupling between t2g orbitals. The proposed mechanism is likely relevant to other multiband superconductors.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Spinon entanglement then effectively "rectifies" the circulating orbital currents, resulting in a macroscopic supercurrent. This mechanism is similar to the one recently proposed for STO, and is likely relevant to other unconventional superconductors [22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Spinon entanglement then effectively "rectifies" the circulating orbital currents, resulting in a macroscopic supercurrent. This mechanism is similar to the one recently proposed for STO, and is likely relevant to other unconventional superconductors [22].…”
Section: Discussionsupporting
confidence: 85%
“…Recent analysis of the electronic properties of STO showed that the bottom of the conduction band in this material is formed by a Kramers doublet of states with unquenched orbital moments and maximal total angular momentum j = 5/2 minimizing the spin-orbit coupling (SOC) energy [22]. Coulomb interaction dominant at small carrier density was shown to stabilize a spin-orbit liquid characterized by polaronic-like electron localization.…”
Section: Introductionmentioning
confidence: 99%